Uric acid and bone mineral density in postmenopausal osteoporotic women: the link lies within the fat. Issue 3 (March 2017) - Pirro, M.; Mannarino, M.; Bianconi, V.; De Vuono, S.; Sahebkar, A.; Bagaglia, F.; Franceschini, L.; Scarponi, A.; Mannarino, E.; Merriman, T.
Abstract Summary The association between serum uric acid (SUA) levels and bone mineral density (BMD) is controversial. Fat accumulation is linked to SUA and BMD, thus possibly explaining the mixed results. We found that adiposity drives part of the association between SUA and BMD in women with postmenopausal osteoporosis. Introduction Both positive and negative associations between SUA and BMD have been reported. SUA levels and BMD increase with higher body weight and other indices of adiposity; hence, the association between SUA and BMD might be a consequence of the confounding effect of adiposity. We investigated in this cross-sectional study whether the association between SUA and BMD is independent of measures of fat accumulation and other potential confounders. Methods SUA levels, femur BMD, markers of bone metabolism, body mass index (BMI), fat mass (FM), waist circumference (WC), and abdominal visceral fat area were measured in 180 treatment-naive postmenopausal osteoporotic women (mean age 66.3 ± 8.5 years, age range 48–81 years). Results Women with higher SUA levels (third tertile) had significantly higher femur BMD and lower cross-linked C-terminal telopeptide of type I collagen (CTX) and bone alkaline phosphatase (bALP) levels. SUA levels were positively associated with all indices of adiposity. In multivariable analysis with femur BMD as dependent variable, the association between logarithmic (LG)-transformed SUA levels and BMD (beta = 0.42, p  < 0.001) was lessened progressively by the different indices of adiposity, like LG-BMI (beta = 0.22, p  = 0.007), LG-WC (beta = 0.21, p  = 0.01), LG-FM (beta = 0.18, p  = 0.01), and LG-abdominal visceral fat area (beta = 0.12, p  = 0.05). The association between SUA levels and markers of bone metabolism was dependent on the effect of confounders. Conclusion In postmenopausal osteoporotic women, the strong univariable association between SUA levels and femur BMD is partly explained by the confounding effect of indices of adiposity.